TRANSPARENT ENERGY HARVESTING ANTENNA FOR VEHICLE WINDSHIELD APPLICATION - Yusnita Rahayu; Muhammad Ikmal; Ahmad Mudhirullaq Syam; Daniel Junianto (SINERGI, 2019)
This paper presents a transparent energy harvesting antenna for a vehicle windshield application. The antenna is designed using AgHT-4 with a thickness of 0.175 mm and the glass substrate (Ɛr= 4.82) with a thickness of 2 mm. The antenna has dimensions of 46.238 x 35.4 mm. The antenna is designed and simulated in CST simulation software. It shows that the return loss of -32.76 dB obtained at 2.2412 GHz with broad directional pattern and a gain of 5 dBi. The rectifier circuit of RF energy harvesting will charge the energy storage by utilizing the ambient RF signals from the environment, convert it to the DC signal, and using the DC signal to charge the energy storage. This antenna is intended to be mounted on a car windshield to provide Wi-Fi signals to passengers